Probability of walking in children with cerebral palsy in Europe - Beckung, Eva; Hagberg, Gudrun; Uldall, Peter; Cans, Christine (Pediatrics (Evanston), 2008)
The purpose of this work was to describe walking ability in children with cerebral palsy from the Surveillance of Cerebral Palsy in Europe common database through 21 years and to examine the association between walking ability and predicting factors. Anonymous data on 10042 children with cerebral palsy born between 1976 and 1996 were gathered from 14 European centers; 9012 patients were eligible for the analyses. Unaided walking as the primary way of walking at 5 years of age was reported for 54%, walking with assistive devices was reported for 16%, and no walking ability was reported for 30%. The proportion of children who were unable to walk was rather stable over time in all of the centers, with a mean proportion of 28%. Walking ability related significantly to cerebral palsy types, that is, spastic unilateral, spastic bilateral, dyskinetic, and ataxic cerebral palsy, as well as to IQ level, active epilepsy, and severe visual and hearing impairment. Severe cerebral palsy, defined as both the inability to walk and an IQ of <50, was present in 20% of the subjects. Logistic regression revealed that intellectual capacity was the variable most associated with walking ability in all 4 of the cerebral palsy types. The presence of a severe intellectual impairment increased the risk of being unable to walk 56 times if the child had unilateral spastic cerebral palsy type and 9 times if the child had bilateral spastic cerebral palsy type. The collaboration Surveillance of Cerebral Palsy in Europe provides a powerful means of monitoring trends in cerebral palsy and its functional consequences. The proportion of nonwalking in children with cerebral palsy seems to be rather stable over years and across centers despite the changes that have occurred in neonatal care across Europe. As is well known and also shown in this study, walking ability varied strongly with cerebral palsy type. Additional impairments, as well as the presence of epilepsy, correlated significantly with walking ability and, thus, the walking ability can be an indicator of total disability load.